Anthropology and Social Theory : Culture, Power, and the Acting Subject - Ortner, Sherry B., 1941- (Book collections on Project MUSE., 2006)
In Anthropology and Social Theory the award-winning anthropologist Sherry B. Ortner draws on her longstanding interest in theories of cultural practice to rethink key concepts of culture, agency, and subjectivity for the social sciences of the twenty-first century. The seven theoretical and interpretive essays in this volume each advocate reconfiguring, rather than abandoning, the concept of culture. Similarly, they all suggest that a theory which depends on the interested action of social beings - specifically practice theory, associated especially with the work of Pierre Bourdieu - requires a more developed notion of human agency and a richer conception of human subjectivity. Ortner shows how social theory must both build upon and move beyond classic practice theory in order to understand the contemporary world. Some of the essays reflect explicitly on theoretical concerns: the relationship between agency and power, the problematic quality of ethnographic studies of resistance, and the possibility of producing an anthropology of subjectivity. Others are ethnographic studies that apply Ortner's theoretical framework. In these, she investigates aspects of social class, looking at the relationship between race and middle-class identity in the United States, the often invisible nature of class as a cultural identity and as an analytical category in social inquiry, and the role that public culture and media play in the creation of the class anxieties of Generation X. Written with Ortner's characteristic lucidity, these essays constitute a major statement about the future of social theory from one of the leading anthropologists of our time.